Aquarium Viromes: Viromes of Human-Managed Aquatic Systems - Kim, Yiseul; Van Bonn, William; Aw, Tiong G.; Rose, Joan B. (Frontiers in Microbiology, 2017)
An aquarium ecosystem is home to many animal species providing conditions similar to native aquatic habitats but under highly controlled management. With a growing interest in understanding the interaction of microbiomes and resident animal health within aquarium environments, we undertook a metagenomic survey of viromes in seven aquarium systems with differing physicochemical and resident animal profiles. Our results show that a diverse array of viruses was represented in aquarium viromes, many of which were widespread in different aquarium systems (27 common viral families in all of the aquarium systems). Most viromes were dominated by DNA phages of the order Caudovirales as commonly found in other aquatic environments with average relative abundance greater than 64%. The composition and structure of aquarium viromes were associated with controlled system parameters, including nitrate, salinity, and temperature as well as resident animal profiles, indicating the close interaction of viromes with aquarium management practices. Furthermore, finding human associated viruses in a touch exhibit suggested that exposure of aquarium systems to human contact may lead to introduction of human cutaneous viruses into aquaria. This is consistent with the high abundance of skin microflora on the palms of healthy individuals and their detection in recreational waters, such as swimming pools. Lastly, assessment of antibiotic resistance genes (ARGs) in aquarium viromes revealed a unique signature of ARGs in different aquarium systems with trimethoprim being the most common. This is the first study to provide vital information on viromes and their unique relationships with management practices in a human-built and controlled aquarium environment.